Creating an Assessment Tool for Clinical Musculoskeletal Knowledge. Issue 2 (February 2021) - Yu, Jonathan; Li, Alexander D.; Leggit, Jeffrey C.
Abstract : Abstract: Studies show that medical school curriculums do not prepare graduates to manage the most common musculoskeletal (MSK) injuries they will encounter in the outpatient setting. The authors proposed a new multiple-choice assessment to identify individual and program deficiencies for curriculum improvement. A multiple-choice MSK assessment tool was administered to learners at various stages of training. Students took the examination after completing their core clerkship year; residents took the examination near the beginning of their respective academic year. Outcome measures included average examination score, percent correct for each question, and overall examination reliability. Average examinees scores were 75.6% with higher scores based on training years. No statistical differences were found between MD/DO, male/female, or military/civilian examinees. The tool was found to be a statistically valid method of determining cognitive knowledge in basic MSK topics, identifying individual deficiencies, and highlighting gaps in training programs' MSK curriculums.